General Biology of Freshwater Prawn, Macrobrachium lamarrei (H. Milne-Edwards) of Biratnagar, Nepal - Sharma, A.; Subba, B.R. (Our Nature, 2006)
Macrobrachium lamarrei (H. Milne-Edward) is commonly known as “kuncho river prawn,” occurring in freshwater ponds and rivers of Biratnagar, Nepal. They are nocturnal species feed voraciously on planktonic organisms, algae, muscles pieces of their own kind or fish etc. M. lamarrei is a medium-sized prawn ranging from 75-80 mm in length rostrum bears 7-9 teeth dorsally and 5-8 ventrally. The estimation of fecundity was done following egg counting method from March, 2004 to February, 2005. The mean fecundity ranged from 82-308 in the prawn having mean body length 57-74 mm and mean bodyweight 0.78-1.62 g. The correlation coefficient (r) of the relationship between body length and fecundity, and body weight and fecundity were 0.201 and 0508 respectively, indicating insignificant relationship. The mean fecundity was found to be 183.55 and mean relative fecundity ranged from 82-221.79. The mature eggs measured 0.54-0.64 mm on its long axis. The suitable temperature recorded during egg laying time was found to be 30±2oC, Do 10 mgl-1 and pH 7.75-8. Marked differences in the morphology and habit of larval stages of prawn ranging from length of body to number of rostral teeth were noted. Key words: Biratnagar, General biology, Macrobrachium lamarrei, Nepal doi:10.3126/on.v3i1.332 Our Nature (2005) 3: 31-41